Telemedicine in Neurosurgery: Lessons Learned and Transformation of Care During COVID-19 - Mouchtouris, Nikolaos (Neurosurgery, 2020)
INTRODUCTION: The COVID-19 national emergency declared in the United States on March 13(th), 2020 dramatically changed the role of telemedicine in clinical care since shelter-in-place orders were issued throughout the country. In an effort to limit the patient and healthcare provider exposure, telemedicine has been an essential platform. As neurosurgical providers interact with patients in the operating room, intensive care unit, emergency department, and outpatient clinics each day, they place themselves as well as their patients at an increased risk of exposure. There is a widespread need for further implementation of telemedicine to reduce viral exposure. METHODS: A single-center retrospective cohort study of patients who received neurosurgical care at a single-center tertiary academic center from February to April 2020 was conducted. Patients evaluated from March to April 2019 were included for comparison. A total of 10,746 patients were included: 1247 patients underwent surgery, 8,742 were seen in clinic via an in-person outpatient visit and 757 were assessed via telemedicine during the study period. RESULTS: A 36-fold increase in the use of telemedicine was noted after the shelter-in-place measures were initiated with a significant increase in the mean number of patients evaluated via telemedicine per week across all divisions of neurosurgery (3.9 ± 3.0 to 141.4 ± 19.8, P < .001). The majority of telemedicine appointments were established patient visits (61.2%), but the proportion of new patient visits also significantly increased to an average of 8.2 ± 5.3 per week across all divisions during the pandemic. CONCLUSION: Experience with telemedicine prior to the COVID-19 pandemic allowed for rapid expansion of our program to meet the needs of our patients once the shelter-in-place measures were ordered. We provide a detailed account of the lessons learned and discuss the anticipated role of telemedicine in surgical practices once the shelter-in-place measures are lifted.